AB0009 The HLA Class I Region in Behçet's Disease: Identifying the Most Relevant Amino Acid Positions. (9th June 2015) - Ortiz-Fernández, L.; Carmona, F.D.; Montes-Cano, M.-A.; García-Lozano, J.-R.; Conde-Jaldόn, M.; Ortego-Centeno, N.; Castillo-Palma, M.-J.; Espinosa, G.; Graña-Gil, G.; Sánchez-Bursόn, J.; Juliá, M.R.; Solans, R.; et al.
Abstract : Background: Behçet's disease (BD) has been consistently associated with HLA class I molecules, specifically, with HLA-B51. However, the role of others HLA class I molecules remains controversial. The current methods of genotyping permit to deduce the HLA typing of a large number of individuals by imputation by using data obtained from high throughput platforms. This approach has improved the knowledge of the association of HLA with the susceptibility to immune-mediated diseases. Objectives: Review of the association of HLA region with BD by comprehensive reanalysis with using a novel imputation method [1, 2]. Methods: The HLA typings of 1794 individuals (277 patients and 1517 healthy controls) were imputed from SNPs genotyping data obtained by Human Immuno DNA Analysis BeadChip Kit (Immunochip). The statistical analyses were performed with PLINK and R. Results: The strongest association signals were observed in the HLA-B region, specifically, rs1050502 represented the highest peak (p=7.73 x 10 -24, OR=4.029, 95%CI 3.123 to 5.198). According to the analysis performed, the amino-acid positions 97 in the HLA-B and 66 HLA-A molecules are the most relevant for the disease susceptibility. Conclusions: HLA-B and HLA-A are associated with the susceptibility to BD References: Raychauduri S, Sandor C, Stahl EA, et al. (2012) Five amino acids in three HLA proteins explain most of the association between MHC and seropositive rheumatoid arthritis. Nat Gen 44, 291-296 Jia X, Han B, Onengut-Gumuscu S, et al. (2013) Imputing amino acid polymorphisms in human leukocyte antigens. PloS one 8, e64683 Disclosure of Interest: None declared